KOMUNIKASI INTERPERSONAL ORANG TUA MUSLIM DALAM PEMBINAAN AKHLAK REMAJA Studi di Kelurahan Way Huwi Jati Agung Lampung Selatan - Nasor, H.M. (Ijtimaiyya: Jurnal Pengembangan Masyarakat Islam, 2015)
Interpersonal communication is the communicationthat takes place between people who areinterdependent and have some knowledge of eachother. It includes what takes place between a son andhis father, a teacher and a student, two friends, and soon. Interpersonal communication is often extended toinclude small intimate groups such as the family.Through this interpersonal communication, parents inWay Huwi Village can build character teenagers,established effective communication and meaningful,and it is able to achieve the goal of fostering moralbehavior in teenagers. Muslims parents build teenagersgood behavior through communication process: thestages of the message, which can affect teenagers'behavior. The parents perceived who has a certaincredibility which trusted by the teenagers. Throughinterpersonal communication, Muslim parents find away to build their teenagers character.